Targeting the ferroptosis pathway for rheumatoid arthritis: molecular mechanisms and prospects for inhibitor development - Wang, Zhuoling; Bai, Xinyue; Zhang, Huahua; Yang, Min; Liu, Meilin; Nie, Tingyu; Li, Tianjiao; Zhang, Mingru; Wang, Xingdan; Wang, Jin; Han, Jiming; Liu, Xiaolong (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease with severe complications. Ferroptosis, an iron-dependent form of apoptosis, encompasses mechanisms including iron overload, lipid peroxidation, redox homeostasis, and reactive oxygen species accumulation, all of which are closely related to RA pathogenesis. This study focused on the mechanism of ferroptosis and RA, detailing their relationship and outlining the reported roles of ferroptosis inhibitors in RA treatment to provide a useful research basis in drug discovery and development and for clinicians.